Updated methodological guidance for the conduct of scoping reviews. Issue 1 (March 2021) - Peters, Micah D.J.; Marnie, Casey; Tricco, Andrea C.; Pollock, Danielle; Munn, Zachary; Alexander, Lyndsay; McInerney, Patricia; Godfrey, Christina M.; Khalil, Hanan
ABSTRACT: Objective: The objective of this paper is to describe the updated methodological guidance for conducting a JBI scoping review, with a focus on new updates to the approach and development of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (the PRISMA-ScR). Introduction: Scoping reviews are an increasingly common approach to informing decision-making and research based on the identification and examination of the literature on a given topic or issue. Scoping reviews draw on evidence from any research methodology and may also include evidence from non-research sources, such as policy. In this manner, scoping reviews provide a comprehensive overview to address broader review questions than traditionally more specific systematic reviews of effectiveness or qualitative evidence. The increasing popularity of scoping reviews has been accompanied by the development of a reporting guideline: the PRISMA-ScR. In 2014, the JBI Scoping Review Methodology Group developed guidance for scoping reviews that received minor updates in 2017 and was most recently updated in 2020. The updates reflect ongoing and substantial developments in approaches to scoping review conduct and reporting. As such, the JBI Scoping Review Methodology Group recognized the need to revise the guidance to align with the current state of knowledge and reporting standards in evidence synthesis. Methods: Between 2015 and 2020, the JBI Scoping Review Methodology Group expanded its membership; extensively reviewed the literature; engaged via annual face-to-face meetings, regular teleconferences, and email correspondence; sought advice from methodological experts; facilitated workshops; and presented at scientific conferences. This process led to updated guidance for scoping reviews published in the JBI Manual for Evidence Synthesis . The updated chapter was endorsed by JBI's International Scientific Committee in 2020. Results: The updated JBI guidance for scoping reviews includes additional guidance on several methodological issues, such as when a scoping review is (or is not) appropriate, and how to extract, analyze, and present results, and provides clarification for implications for practice and research. Furthermore, it is aligned with the PRISMA-ScR to ensure consistent reporting. Conclusions: The latest JBI guidance for scoping reviews provides up-to-date guidance that can be used by authors when conducting a scoping review. Furthermore, it aligns with the PRISMA-ScR, which can be used to report the conduct of a scoping review. A series of ongoing and future methodological projects identified by the JBI Scoping Review Methodology Group to further refine the methodology are planned.